ANALISIS PERUBAHAN TUTUPAN LAHAN DI AREAL IUPHHK-RE PT. GEMILANG CIPTA NUSANTARA KABUPATEN PELALAWAN - Dibyo Kuswiyono; Nofrizal; Nurul Qomar (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2020)
The research was conducted at March to June 2020 and located in IUPHHK-RE PT. Gemilang Cipta Nusantara Pelalawan Regency Riau Province. This research aims to describing and analyze the changed of the land cover in IUPHHK-RE PT. Gemilang Cipta Nusantara Pelalawan Regency. Based on the result of this research, there are five (5) types of the land cover that is: secondary swamp forest, old secondary swamp forest, young secondary swamp forest, watersheds and infrastructure. The condition of land cover in IUPHHK-RE PT. Gemilang Cipta Nusantara a bit changed compared with previous, there is an open area about 33,97 hectars due to forest fires at 2014 and constructed road to Green House Gas (GHG) Flux Monitoring Tower about 5,83 hectars at 2017.